Evaluación de la producción de Piñón Blanco (Jatropha Curcas l.) con tres densidades de siembra y tres tipos de podas en el distrito de la Banda de Shilcayo San Martín Perú - Manrique García, Arlek (2013)
For the aim of determining the best-suited sowing density that allows the increase of White Pine yield (Jatropha curcas L.) as well as the suitable methodology in order to elders's generation productive branches in the White Pine kernel's culture, three planting densities were evaluated (3 m x 1,5 m; 3 m x 2 m and 3 m x 3 m) associate to three kind of pruning (3 sprouts; 1 sprout plus 2 pruning and 3 pruning); with respective proof (without pruning or sprouts) just using a Block Design Completely at Random (DBCA) with 3 x 4 factorial arrangement. It was evaluated a 12 treatments total, included the proof treatments. It was found that the best-suited planting distance was 3 x 2, as for the type of pruning the treatment 3th sprouts obtained better outputs, as for the early beginning in flowering, bigger branches and yield number, nevertheless, the proof treatment got one of the best outputs, however, a non pruning plant does a very difficult harvest added up to the poor entry of light and biggest competition for space among the plants that could involve a fast decrease of yield same as happens under natural conditions.